1971
DOI: 10.1084/jem.133.3.572
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Pulmonary Methane Excretion in Man

Abstract: It is becoming increasingly apparent that the metabolic activity of the normal intestinal flora may exert a profound influence on the physiology of their host (1). There is, however, only limited information concerning the metabolism of these bacteria, and this information has been derived primarily from studies carried out with isolated species in culture media. The results of such studies may not accurately reflect the in situ behavior of these organisms within the complex environment of the bowel.In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
144
2
6

Year Published

1983
1983
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(160 citation statements)
references
References 17 publications
8
144
2
6
Order By: Relevance
“…Although breath methane reliably reflects the abundance of colonic methanogens, non-methanogenic subjects, as thereby defined, often harbor a relatively lower number of stool MA (El Oufir et al, 1996). One study, based on a fortuitous measurement of colonic gases, suggested that methane was predominantly produced in the left colon (Bond et al, 1971). Culture-based data consistent with the abundance of MA increasing in a proximal to distal gradient have also been reported (Macfarlane et al, 1992).…”
Section: Discussionmentioning
confidence: 63%
“…Although breath methane reliably reflects the abundance of colonic methanogens, non-methanogenic subjects, as thereby defined, often harbor a relatively lower number of stool MA (El Oufir et al, 1996). One study, based on a fortuitous measurement of colonic gases, suggested that methane was predominantly produced in the left colon (Bond et al, 1971). Culture-based data consistent with the abundance of MA increasing in a proximal to distal gradient have also been reported (Macfarlane et al, 1992).…”
Section: Discussionmentioning
confidence: 63%
“…Thirty to fifty percent of humans are positive for methanogens in the gut as measured either by breath tests (10,11) or PCR assays targeting mcrA (methyl coenzyme M reductase subunit A, conserved in the methanogenesis pathway) (12). However, whether and how host physiologic factors, such as gastrointestinal transit time (13,14) and BMI (15,16), influence interpersonal variation in the representation of methanogens remains unclear.…”
mentioning
confidence: 99%
“…Methanobrevibacter smithii is the most prominent methanogen in the human gastrointestinal tract and has been found at concentrations of 10 7 to 10 10 organisms · g Ϫ1 in feces (12,35). The use of the nifH gene of M. smithii to identify human-associated fecal pollution has been limited but successful in MST studies conducted to date (23,55), as it is relatively host specific compared to some other MST markers (3,23,31).…”
mentioning
confidence: 99%